Candida Species Profile of Vulvovaginal Candidiasis in HIV/AIDS Patients Treated With Systemic Antibiotic - Widasmara, Dhelya; Suyoso, Sunarso; Murtiastutik, Dwi (Faculty Of Medicine Airlangga University, 2014)
Background: Vulvovaginalis Candidiasis (VVC) is a vulva and vaginal infection of Candida, which one of predisposition factors is systemic antibiotics. Humoral immunity does not play a role on VVC, thus VVC in HIV/AIDS patients is as much as VVC in immunocompetent patient. Purpose: Identify the profile of Candida sp. of VVC in HIV/AIDS patients who got systemic antibiotics. Methods: Descriptional study to identify the pattern of Candida sp. of VVC in HIV/AIDS patient who got systemic antibiotic with cultures of Saboroud Dextrose Agar, Cornmeal Tween80 with Carbohydrat Test and Candida CHROM agar. Results: Broad-spectrum antibiotics were given to HIV/AIDS patient with VVC at Dr. Soetomo general hospital Surabaya two times higher than narrow-spectrum antibiotics (66,7% vs. 33,3%), they were ciprofloxacin (42,8%), ceftazidime (19,1%) and ceftriaxone (4,8%); theÂ narrow-spectrum antibiotics were cotrimoxazole (19,0%) and rifampicin (14,3%). Conclusion: C.albicans (57,1%) and C. glabrata (9,6%) were found in VVC of HIV/AIDS patients that have been given broad-spectrum antibiotics, while C. albicans (28,6%) & C. glabrata (4,7%) also found in VVC of HIV/AIDS patients that have been given narrow-spectrum antibiotics. C. dubliniensis were not found in this studyKey words: Candida spp, vulvovaginal candidiasis, HIV/AIDS, antibiotics